Percepções das práticas colaborativas entre professores do ensino comum e de Educação Especial em escolas de Educação Infantil - Bueno, Adriana Correa (2024)
Early Childhood Education schools are environments that provide learning and development for all students, with and without disabilities. Thinking about their spaces, times, pedagogical resources and ensuring collaboration between professionals involved in the learning process, who work in these environments, especially with children who are the target audience for special education, is the theme of this research. How have teachers implemented their practices with target children for Special Education in Stage I of Early Childhood Education? Considering the official guidelines and the importance of collaboration in the educacional context, is it feasible to carry out collaborative practices between regular education and Special Education teachers in Early Childhood Education schools- Stage I? This study aims to analyze, together with regular education and Special Education teachers who work in Early Childhood Education - Stage I (from 0 to 3 years old), the perception regarding the collaborative practices developed and how they are constituted among these professionals. It is research based on the qualitative approach and assumptions of collaborative research. The research was developed in a municipality in the interior of São Paulo and in the first stage, a questionnaire was applied to 38 teachers (common education and Special Education teachers), who worked in public Early Childhood Education schools - Stage I, with children between 0 and 3 years of age, with the aim of obtaining a characterization of the structure relating to the organization of AEE and the dynamics between them in regular education, identifying concepts, challenges and practices present in everyday school life; and in a second moment, 14 teachers were selected to carry out 6 reflective sessions, in which participants had the chance to reflect and reorganize their practices, in order to enhance it. In this age group, the practices identified that require greater collaboration include assistance in referring students for evaluation in the health area and behavioral issues that hinder the effective participation of some students. The results obtained in the research highlighted the lack of standardization with regard to the duration, format and structure of Specialized Educational Assistance aimed at children Targeted by Special Education in Early Childhood Education - Stage I schools (from 0 to 3 years old). Additionally, it was found that there is no educational policy, or legislation, that consistently endorses the existing guidelines on AEE in Early Childhood Education schools - Stage I. We highlight that there is an attempt to implement collaborative practices between these teachers and the school team, as a whole, although, timidly, the culture of collaboration is beginning to manifest itself in these schools. However, for these practices to develop effectively, a change in the conceptions and practices of all professionals involved is imperative, and such a transition encounters significant obstacles in various aspects of daily school life, such as resistance from both types of teachers, lack of of time, lack of resources and AEE teachers in all schools, among many others. It is concluded that it is essential to reorganize the educational environment with the aim of promoting practices among educators and making proposals for continued training on how to work collaboratively in this age group, thus strengthening school inclusion.